Pengaruh Model Discovery Learning Berbantuan LKPD Multirepresentasi terhadap Keterampilan Argumentasi Ilmiah Siswa SMP pada Pembelajaran IPA - Agustiyani, Silvia; Supeno; Budiani, Lilik (PendIPA Journal of Science Education, 2025)
The scientific argumentation skills of junior high school students are still at a low level, especially in constructing claims, data, and warrants, due to teacher-centered learning. This study examines the effect of the discovery learning model supported by multirepresentation worksheets on students’ scientific argumentation skills. The method used was quasi-experimental with a non-equivalent control group design in two seventh grade classes at SMPN 6 Jember. Data were obtained through descriptive test and analyzed using normality, homogenity, and independent sample t-test. The statistical test results showed a significance value of 0.001 (<0.05), indicating that the discovery learning model supported by multirepresentational worksheets had a significant effect on students’scientific argumentation skills in science learning.